Rediscovery of Thismia neptunis (Thismiaceae) after 151 years - Sochor, Michal; Egertová, Zuzana; Hroneš, Michal; Dančák, Martin (Phytotaxa, 2018)
Thismia neptunis, as many of its congeners, is a poorly understood species that has only been known from the type collection and its limited original description. In January 2017 it was rediscovered in the type area in the Gunung Matang massif, western Sarawak, Borneo, Malaysia. The paper provides the amended description and drawings of the species, very first available photographs and short notes on taxonomy and historical context of Beccari’s work on Thismia.